Cultivate Conference 2016 - Austin, TX : Video Compilation (O'Reilly Media, Inc., 2016)
Cultivate Austin 2016 is the Texas flavored version of O'Reilly's 2-day leadership training. This 12-session video compilation features a group of speakers as Austin-y and idiosyncratic as taco truck migas or an afternoon at Barton Springs. Yes, the speakers are heavily degreed. Yes, they've toiled in the tech world hothouses of Oracle and Google et al. Yes, they've led start-ups and consulted to the Bigs. But just as important are the unique life experiences they bring that spice their talks and make you want to watch. A 35-year veteran of conflict resolution and peace studies. A writer for a motorcycle culture and lifestyle magazine. An advisor to the Environmental Defense Fund. A transgender activist. A protégé of the creator of MSTK3. And lots more. It's a refreshing idea ensalada , Austin style. Get all twelve sessions from Cultivate Austin 2016 Hear inspirational talks on business leadership, entrepreneurship, hiring and conflict resolution Watch how playing with LEGO®s weaves disparate thinkers into a cohesive team Hear why resumes and white board coding interviews suck and what you can do better Understand why the open source philosophy of transparency, fairness, and merit drives success Receive practical advice for managing multicultural teams across campuses and continents Download the videos or view them through our HD player.